Lanthanide Contraction as a Design Factor for High-Performance Half-Heusler Thermoelectric Materials - Liu, Yintu; Fu, Chenguang; Xia, Kaiyang; Yu, Junjie; Zhao, Xinbing; Pan, Hongge; Felser, Claudia; Zhu, Tiejun (Advanced Materials, 2018)
Forming solid solutions, as an effective strategy to improve thermoelectric performance, has a dilemma that alloy scattering will reduce both the thermal conductivity and carrier mobility. Here, an intuitive way is proposed to decouple the opposite effects, that is, using lanthanide contraction as a design factor to select alloying atoms with large mass fluctuation but small radius difference from the host atoms. Typical half-Heusler alloys, n-type (Zr,Hf)NiSn and p-type (Nb,Ta)FeSb solid solutions, are taken as paradigms to attest the validity of this design strategy, which exhibit greatly suppressed lattice thermal conductivity and maintained carrier mobility. Furthermore, by considering lanthanide contraction, n-type (Zr,Hf)CoSb-based alloys with high zT of ≈1.0 are developed. These results highlight the significance of lanthanide contraction as a design factor in enhancing the thermoelectric performance and reveal the practical potential of (Zr,Hf)CoSb-based half-Heusler compounds due to the matched n-type and p-type thermoelectric performance.
CRIS-Team Scopus Importer:2022-04-14
Keywords: alloy scattering; half-Heusler; lanthanide contraction; thermoelectrics